(untitled) - Nwagboso, Christopher O.; Christopher O. Nwagboso (Chichester)
This book explores the technical advances in vehicle and infrastructure systems that are taking place in response to the increasing congestion of our roads. It describes all the relevant computer and control techniques and takes an applications-oriented approach to fill the many gaps that exist in the mass knowledge in the field
Includes bilbiographical references and index
Keywords: Intelligent transportation systems; Motor vehicles; Motor vehicles; Automobile driving